KEPEMIMPINAN POLITIK PEREMPUAN DALAM PANDANGAN ISLAM - Mashuri Mashuri (UIN Sunan Kalijaga Yogyakarta, 2016)
The discussions and discourses about women leadership are never ending to be observed, both in common people as well as in the elites. There is a view that woman could be a leader with argument that woman leadership is possible as long as for the goodnessofpeople. Islamic thought recognizesmen's and women's